The Effect of Placement and Career Development on Employee Performance of PT. Mandiri Karya in Jakarta - Ade Muslimat (Program Pascasarjana Universitas Negeri Makassar, 2020)
This study aims to determine the effect of career placement and development on employee performance at PT. Mandiri Karya in Jakarta. The method used is explanatory research with analytical techniques using statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study the placement of a significant effect on employee performance by 41.6%, the hypothesis test obtained t count> t table or (8,133> 1,986). Career development has a significant effect on employee performance by 43.8%, the hypothesis test is obtained t count> t table or (8.508> 1.986). Career placement and development simultaneously have a significant effect on employee performance by 52.6%, the hypothesis test is obtained F count> F table or (51.106> 2,700).